2011
DOI: 10.1002/clen.201000510
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Lead in PM2.5 after Leaded Gasoline Phase‐out in Jeddah City, Saudi Arabia

Abstract: . The collected PM 2.5 -samples were analyzed by ICP-MS for determination of lead. The average atmospheric PM 2.5 concentration was 50.8 mg/m 3 . Atmospheric PM 2.5 -concentrations were higher than the 24-h U.S. National Ambient Air Quality Standards (NAAQS) in 14 sample events. The average lead concentration for all samples was 0.07326 mg/m 3 . Atmospheric lead concentration was dependent on the sampling location. Concentrations at the two southern locations were higher than at the two northern locations. Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…It was found that the highest Pb concentrations in the residential, industrial, and traffic dominated sites were found during October 2011, March 2012 and May 2012. The relatively low Pb concentration in PM 2.5 particles in Taif city would refer to the banning of leaded gasoline in Saudi cities (Abulfaraj et al, 1999;Aburas et al, 2011). Based on Köppen-Geiger climate classification system (Peel et al, 2007), Taif city has arid or hot desert climate (Bwh), giving Taif a hot and dry summer and warm and dry winter.…”
Section: Trace Element Concentrationsmentioning
confidence: 99%
“…It was found that the highest Pb concentrations in the residential, industrial, and traffic dominated sites were found during October 2011, March 2012 and May 2012. The relatively low Pb concentration in PM 2.5 particles in Taif city would refer to the banning of leaded gasoline in Saudi cities (Abulfaraj et al, 1999;Aburas et al, 2011). Based on Köppen-Geiger climate classification system (Peel et al, 2007), Taif city has arid or hot desert climate (Bwh), giving Taif a hot and dry summer and warm and dry winter.…”
Section: Trace Element Concentrationsmentioning
confidence: 99%
“…Several studies have been conducted to assess concentrations of total suspended particulates (TSP) and/or PM10, as well as their lead content (Nasrallah, 1984, Abulfaraj, et al ., 1990, and Al-Jeelani, 1996). The PM2.5 studies are either limited to a specific component such lead in Saudi Arabia after leaded gasoline phase-out (Aburas, et al ., 2011), or specific source, such as a study on roadside soil pollution (Kadi, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the city's system for collecting and managing solid waste is not optimal, and much of it is burned under un-controlled conditions, presenting a significant health hazard. Studies on atmospheric particulate matter and volatile organic compounds have been conducted in different cities in Saudi Arabia (Abulfaraf et al, 1990;Sabbak, 1990;Al-Jeelani, 2009;Aburas et al, 2011), but aside from a study on airborne bacteria (Mahdy and ElSehrawi, 1997), there have been no investigations into particulate pollution in Taif.…”
Section: Introductionmentioning
confidence: 99%